Comprehensive analysis of the effects of high stocking density stress on broiler health - Bai, Dongying; Guo, Caifang; Ma, Penghui; Wang, Ziwei; Zhao, Xiaodie; Ma, Xiqiang; Xie, Xiaolin; Zhang, Yi; Guo, Fangshen; Zhang, Yushu; Zhang, Bingkun; Zhang, Cai; et al. (Frontiers in Veterinary Science, 2026)
High stocking density (HSD) stress is a serious risk factor for poor animal health and loss of commercial productivity that affects broiler farms globally. While HSD can increase production efficiency and reduce costs, it can also lead to aggressive behavior and competition among the animals, unequal resource distribution, increased stress, disease, and loss of meat quality. Under HSD stress conditions, the redox balance is disrupted, inflammatory responses are exacerbated, immune function is impaired, and susceptibility to disease increases. This study reviewed the effects of HSD on the health of broilers, analyzing and prioritizing the associated physiological and biochemical changes. This review focuses on broiler chickens. HSD can have multiple adverse effects on poultry health, and this review evaluates nutritional strategies aimed at alleviating the negative effects of HSD stress to enhance welfare and productivity. By synthesizing current evidence, this review highlights the impacts of HSD on broiler health and welfare and identifies opportunities for nutritional interventions to mitigate these effects. This review provides a comprehensive reference for future research of HSD stress in poultry.